Development of a single-tube one-step RT-LAMP assay to detect the Chikungunya virus genome - Lopez-Jimena, Benjamin; Wehner, Stefanie; Harold, Graham; Bakheit, Mohammed; Frischmann, Sieghard; Bekaert, Michaël; Faye, Oumar; Sall, Amadou Alpha; Weidmann, Manfred (PLOS Neglected Tropical Diseases, 2018)
Author summary Current chikungunya virus (CHIKV) outbreaks highlight the necessity of sensitive techniques to allow the virus detection even at an early stage (before the onset of clinical symptoms). In addition, CHIKV sometimes is misdiagnosed with other pathogens (i.e., dengue virus or malaria), which implies that specific methods have to be developed. Apart from specificity and sensitivity, these techniques have to be affordable for laboratories with very limited resources, and reactions should be easily performed without the need of experienced researchers and expensive equipment. Finally, because of the increase in number of publicly available sequences, the assay should cover all the possible variations observed in those sequences. We have considered all these premises, and we were able to develop a reverse transcription loop-mediated isothermal amplification (RT-LAMP) by designing primers using a combination of Principal Component Analysis, phylogenetic analysis and LAVA algorithm. Our assay is specific and does not cross-react with other arboviruses tested, sensitive and has been validated at the Institut Pasteur Dakar, showing very good performance parameters.